Preserving Intangible Islamic Heritage: Poetic and Aesthetic Expressions of Dikir Burdah in Sarawak, Malaysia - Mawar Suhaila, Ab Razak; Laura Prati, Tutom (-, 2025)
This study explores the role of Dikir Burdah (DB), a traditional Malay devotional performance, in preserving the intangible Islamic cultural heritage of the Malay-Muslim community in Kampung Hulu, Sri Aman, Sarawak, Malaysia (KHSASM). Combining poetic literature, spiritual expression, and musical aesthetics, DB represents a unique heritage form deeply embedded within local identity and intergenerational transmission. Using a qualitative ethnographic approach, in-depth interviews, content analysis of original poetic lyrics, and direct observation of performances, this research investigates how aesthetic and poetic dimensions of DB contribute to cultural continuity and spiritual well-being. The findings highlight the lyrics' performative and meditative value, the art form's communal function, and the challenges posed by modernization and declining practice among younger generations. This paper contributes to discussions on safeguarding intangible Islamic cultural heritage by emphasizing the importance of local poetic traditions and culturally embedded art forms in sustaining cultural identity and communal resilience. It also proposes culturally sensitive documentation, revitalization, and policy integration strategies in heritage preservation.